DYNAMIC PARAMETERS OF ISSYK-KUL LAKE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The results of experimental research of variable parameters of Issyk-Kul are presentedin this paper. This paper presents the results of field studies and the results of numerical calculationsof the changing biogenic parameters of lake Issyk-Kul. The developed mathematical model of thedynamics of the biomass of phytoplankton in built methods for evaluation of chlorophyll content,given its distribution and depth depending on the different cases of light penetration. Based on theprocessing of satellite images of lake Issyk Kul in different ranges, data on the increase in the areaof biogenic materials on the surface of lake Issyk Kul were obtained for the first time.
Keywords: Issyk-kul lake, phytoplankton, biogenic substance, GIS-technologies, chlorophyll, light absorption.